Una nova aportació per a la prosa catalana del Barroc: el Capritxo de fra Tomàs Roca. - Climent, Joan Mahiques (Zeitschrift für Katalanistik, 2022)
This paper studies and edits the Capritxo by Friar Tomàs Roca, an almost unknown work of Catalan Baroque prose. The Capritxo is a 17th-century epistolary novel copied in the ms. 788 of the Biblioteca Valenciana Nicolau Primitiu. Due to its characteristics, this work can be compared to the Estil·lades i amoroses lletres trameses per Bertomeu Cirlot a la sua senyora i per ella a ell. The Capritxo consists of three letters written by the graduate Sophistice plus a response from the Dr Syncathegorematice to the first mail of the former. This exchange of letters draws a story about the misfortunes of two rogues sentenced to galleys. Several Latin words, especially adverbial phrases, are regularly inserted into Capritxo's Catalan text, thus parodying the scholastic and grandiloquent language of theologians and magistrates, and joking with wordplays which may be related to the meaning of both senders' names. Moreover, the Capritxo criticizes not only the disproportionate severity of the torture and the sentences applied against many galley prisoners, but also the inhibition of some powerful people faced with such injustices.